A statistical reconstruction model for absorption CT with source uncertainty. (27th July 2021) - Bangsgaard, Katrine O; Andersen, Martin S
Abstract: Reconstruction methods for computed tomography are often based on the assumption that the source intensity and the detector response are known and static. In practice, however, both are unknown and must be estimated. An estimate of the combined source intensity and detector response is typically obtained by acquiring a number of so-called flat-field measurements, but this approach is oblivious to intensity drift, e.g. due to source instabilities, vibrating beamline components, etc. Discrepancies between the estimated response and true response can lead to severe artifacts in the reconstruction, especially for dose- and/or time-limited experiments. We propose a new, extended reconstruction model that jointly estimates the reconstruction, the detector response, and the (possibly time-varying) source intensity. We demonstrate through simulated experiments that the proposed reconstruction model leads to reconstructions with significantly reduced artifacts.